Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1164/rccm.200412-1687oc
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae from Patients with Chronic Obstructive Pulmonary Disease Exacerbation Induce More Inflammation than Colonizers

Abstract: The results indicate that H. influenzae strains isolated from patients during COPD exacerbations often induce more airway inflammation and likely have differences in virulence compared with colonizing strains. These findings support the concept that bacteria infecting the airway during COPD exacerbations mediate increased airway inflammation and contribute to decreased airway function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 49 publications
7
105
1
6
Order By: Relevance
“…Interestingly, new H. influenzae strains associated with symptomatic exacerbations resulted in increased neutrophil recruitment in a mouse model of airway bacterial infection as well as greater adherence to epithelial cells and induction of IL-8 release than strains not associated with such a clinical response (82). Similar data have been published regarding M. catarrhalis (83).…”
Section: Bacteriasupporting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, new H. influenzae strains associated with symptomatic exacerbations resulted in increased neutrophil recruitment in a mouse model of airway bacterial infection as well as greater adherence to epithelial cells and induction of IL-8 release than strains not associated with such a clinical response (82). Similar data have been published regarding M. catarrhalis (83).…”
Section: Bacteriasupporting
confidence: 61%
“…Recent longitudinal cohort studies, using analyses of surface antigen diversity, have demonstrated that acquisition of a bacterial strain with which the patient had not been previously infected was associated with a greater than twofold increase in exacerbation risk (81,82). Interestingly, new H. influenzae strains associated with symptomatic exacerbations resulted in increased neutrophil recruitment in a mouse model of airway bacterial infection as well as greater adherence to epithelial cells and induction of IL-8 release than strains not associated with such a clinical response (82).…”
Section: Bacteriamentioning
confidence: 99%
“…This indicates that the appearance of specific bacterial strains may play a greater role in the manifestation of chronic lung disease than the total relative abundance of different genera. In support of this finding, strains of H. influenzae isolated from patients with COPD exacerbations have been shown to induce more airway inflammation in mice and in human tracheobronchial epithelial cells than non-COPD isolates, independently of bacterial inoculum size [61]. Understanding the events leading to colonisation by H. influenzae and S. pneumoniae of the lower respiratory tract of COPD patients and to subsequent increased local and systemic inflammation would greatly enhance our understanding of AECOPD.…”
Section: Bacterial Infection As a Trigger For Acute Exacerbations Of mentioning
confidence: 84%
“…Cells were treated on the apical or basolateral surface with the following mediators: 100 U/ml recombinant human IFN-␥ (a gift from Genentech) for 30 min to induce Stat1 phosphorylation, 1000 U/ml recombinant human IFN-␣ 2a (PBL Biomedical Laboratories) for 30 min to induce Stat2 phosphorylation, 1000 U/ml recombinant human IL-4 (R&D Systems) for 30 min to induce Stat6 phosphorylation, or 100 U/ml recombinant human TNF-␣ (R&D Systems) for 24 h to induce IL-8 release and NF-B activation. Some cells were treated on the apical or basolateral surface with equivalent inoculums (10 8 -10 9 CFU/ml, 500 -5000 CFU/epithelial cell) of gentamicin-treated nontypeable H. influenzae strain 12 for 24 h to induce NF-B activation as described previously (16). For epithelia treated at the apical surface, mediator in a medium volume equal to that at the basolateral surface was added.…”
Section: Airway Epithelial Cell Isolation Culture and Treatmentsmentioning
confidence: 99%
“…IL-8 protein concentrations in equal volumes of medium incubated on the apical or basolateral surface of epithelia were determined using a commercial sandwich enzyme-linked immunoassay kit (R&D Systems) as described previously (10,11,16). According to the manufacturer, the sensitivity of this assay system for IL-8 is Ͻ10 pg/ml.…”
Section: Enzyme-linked Immunoassaymentioning
confidence: 99%